Synergistic Antitumor Activity of Camptothecin-Doxorubicin Combinations and their Conjugates with Hyaluronic Acid - Camacho, Kathryn M. (J Control Release, 2015)
Combinations of topoisomerase inhibitors I and II have been found to synergistically inhibit cancer cell growth in vitro, yet clinical studies of these types of combinations have not progressed beyond phase II trials. The results of clinical combinations of topoisomerase (top) I and II inhibitors typically fall within one of two categories: little to no improvement in therapeutic efficacy, or augmented toxicity compared to the single drug counterparts. Hence, despite the promising activity of top I and II inhibitor combinations in vitro, their clinical applicability has not been realized. Here, we report the use of polymer-drug conjugates as a means to co-deliver synergistic doses of top I and II inhibitors camptothecin (CPT) and doxorubicin (DOX) to tumors in vivo in a 4T1 breast cancer model. At specific molar ratios, DOX and CPT were found to be among the most synergistic combinations reported to date, with combination indices between 0.01 and 0.1. The identified optimal ratios were controllably conjugated to hyaluronic acid, and elicited significant tumor reduction of murine 4T1 breast cancer model when administered intravenously. This study elucidates a method to identify synergistic drug combinations and translate them to in vivo by preserving the synergistic ratio via conjugation to a carrier polymer, thus opening a promising approach to translate drug combinations to clinically viable treatment regimens.